Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T17:39:22+01:00
A)
(x+1)(x+8)=(x+3)(x+5)
x²+8+x+8x=x²+3x+5x+15
x²+8+9x=x²+8x+15
x=7

b)
(x-4)²-1=(x-3)(x-2)
x²-8x+16-1=x²-3x-2x+6
-3x=-9
x=3

c)
(x-2)²-x(x-4)=4(x-3)
x²-4x+4-x²+4x=4x-12
16=4x
x=4

d)
(x-9)(x-5)=x²+56-14x
x²-9x-5x+45=x²+56-14x
45=56
RÓWNANIE NIE MA ROZWIĄZANIA

e)
x²-(x+3)(x+4)=x+20
x²-(x²+3x+4x+12)=x+20
x²-x²-3x-4x-12=x+20
-8x=32
x=-4

f)
(x-1)(x+1)-x(x+2)-1=2(x+1)
x²-1-x²-2x-1=2x+2
-4x=4
x=-1

g)
4(x+2)²=(2x-1)(2x+1)-2(2x-1)
4(x²+4x+4)=4x²-1-4x+2
4x²+16x+16=4x²-4x+1
20x=-15
x=-¾
1 5 1